Human factors in land use planning and urban design : methods, practical guidance and applications - Stevens, Nicholas J.; Salmon, Paul M.; Walker, Guy; Stanton, Neville A. 1960- (Boca Raton, FL : CRC Press, 2018)
"This book furthers the role of human factors methods in land use planning and urban design that was recognised by Stevens and Salmon in 2014. At a simplistic level the issues found in both discipline areas are one and the same: the design of the environment brings about emergent behaviours that in some cases are not optimal. Such inquiries are often described as humans and systems not behaving as they were expected to; problems which impact overall system performance, and often issues that have been resistant to a range of an ongoing technical interventions. The same is true for many of the challenges in land use planning and design, including crime prevention and safe cities, the prioritisation of walkable and cycleable neighbourhoods, or the design and implementation of enduring, accessible and attractive public open space."
Preface Acknowledgments Authors Chapter 1 Introduction to Human Factors Methods in Land Use Planning and Urban Design Chapter 2 Data Collection Methods Chapter 3 Task Analysis Methods Chapter 4 Cognitive Task Analysis Methods Chapter 5 Error Identification Methods Chapter 6 Accident Analysis Methods Chapter 7 Situation Awareness Assessment Chapter 8 Mental Workload Assessment Methods Chapter 9 Interface Evaluation Methods Chapter 10 Systems Analysis and Design Methods Chapter 11 Future Human Factors Applications in Land Use Planning and Urban Design References Index
ARC
Book Finder
Keywords: City planning; Land use -- Planning; Regional planning; Human engineering